Volatile organic compounds induced by simulated herbivory in sugarcane plants - Oliveira, Demetrios José Albuquerque; Ribeiro, Thyago Fernado Lisboa; Ribeiro Junior, Karlos Antônio Lisboa; Costa, João Gomes da; Oliveira, Jaim Simões de; Goulart, Henrique Fonseca (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Sugarcane is a crop of great importance for agriculture and the Brazilian economy. This crop can be attacked by several pests that cause severe economic damage in terms of productivity. This work aimed to investigate the volatile compounds released by sugarcane plants submitted to two treatments of simulated herbivory. In the Single Simulated Herbivory (SSH), the plant is mechanically damaged only once, however in the Double Simulated Herbivory (DSH), the plants are mechanically damaged twice. The experiments were evaluated at three different times (24, 48, and 72 hours). The plants presented different profiles of VOCs when submitted to the treatments. The (Z)-jasmone and sulcatone were emitted in greater quantity by the plants of the HSD treatment after 24 and 48 hours of induction, and 48 hours after the induction this compound showed a significant difference to the quantity emitted by the plants of the HSU treatment. These findings indicate that plants can implement defenses against herbivore attacks, by emitting compounds that repel insects and attract parasitoids and or predators.